Eksistensi Tradisi Kajekan bagi Masyarakat Desa Sukodadi Kecamatan Paiton Kabupaten Probolinggo Jawa Timur pada Era Modern - Moh. Alawy Sayfi; . Aliffiati; I Nyoman Suarsana (Department of Anthropology Udayana University, 2022)
A community tradition can’t be ascertained its existence. The kajekan tradition is one of mutual cooperation traditions carried out by the people of Sukodadi Village. In this study, using descriptive exploratory qualitative methods, data collection techniques Informant purposive non-random sampling, observation, interviews and documentation studies. The analysis of this research problem uses the principle of reciprocity theory. The results of this study reveal that the existence of this kajekan tradition still exists, but there are also those who don’t want to. The presence of the modern era is a factor in changing people's understanding in Sukodadi Village. The kajekan tradition is mutual assistance in building someone's house or cleaning around the house, or something similar. This tradition was formed due to the socio-cultural conditions of the people who tend to have high solidarity with one another. However, kajekan is an important mutual cooperation tradition because it has cultural, social, and religious meanings that are closely related to the people of Sukodadi Village. And have values that are upheld by the local community.